2009
DOI: 10.5688/aj730583
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Pharmacy Students' Attendance Decisions in Large Lectures

Abstract: Objectives. To identify reasons for pharmacy student attendance and absenteeism in large lectures and to determine whether certain student characteristics affect student absenteeism. Methods. Pharmacy students' reasons to attend and not attend 3 large lecture courses were identified. Using a Web-based survey instrument, second-year pharmacy students were asked to rate to what degree various reasons affected their decision to attend or not attend classes for 3 courses. Bivariate analyses were used to assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 24 publications
3
55
2
Order By: Relevance
“…7,14 Absenteeism is especially concerning in health professions programs because it is associated with poorer academic performance, may decrease morale of educators and students who attend class, and may necessitate repetition of information for those who missed previous lectures. 13 American…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,14 Absenteeism is especially concerning in health professions programs because it is associated with poorer academic performance, may decrease morale of educators and students who attend class, and may necessitate repetition of information for those who missed previous lectures. 13 American…”
Section: Discussionmentioning
confidence: 99%
“…The reasons that pharmacy students report missing live class sessions include illness, tiredness, work related to other courses, not learning during class, attendance not impacting course grade, course content being available from another source, and a low level of course difficulty. 13 Educators concerned with course attendance may choose to incorporate motivating factors for live class attendance, such as pop quizzes and interactive class sessions. Additionally, some argue the decision to record lectures should not be based on the effect on class attendance but on whether it facilitates student learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 One study showed that 80% of medical students chose to attend specific lectures dependent on the lecture topic itself, while another found that 69% of students cite interest in the topic as a key reason for attendance. 53,54 Even though the argument on the comparative benefits of different instructional designs (e.g., small group discussion, problem based learning, lectures, tutorials, practical demonstrations, and bed side clinical teaching) continues 11 ,skipping class is expected to be unbeneficial for learning even the best and most sophisticated instructional designs used by educators. Even lecture-based teaching seems to provide substantial benefits for learning to take place despite its didactic in nature 55 , poor feedback, and inability to engage in authentic practice.…”
Section: Factors Related To Teaching Stuffmentioning
confidence: 99%
“…In the same study, negative variables that contributed to poor classroom attendance included the class being either before or after an examination in another course, faculty members who do not supplement their provided notes, personal logistics, and extended breaks of 2 hours or more between classes. A second study of pharmacy students by Westrick and colleagues 10 identified that the primary reasons students come to class is a desire to take their own notes and an impression that the instructor might provide information as to what was most important to study from the volume of information presented. Emphasizing the importance of what motivates students can also be seen in the latest ACPE standards.…”
Section: Introductionmentioning
confidence: 99%